THE EFFECT OF CURRENT RATIO, RETURN ON ASSETS, AND DEBT TO EQUITY RATIO ON FINANCIAL DISTRESS IN PT HM SAMPOERNA TBK - Irnawati, Jeni; Asyidiq, Hasbi; Rismanty, Vidya Amalia (Yayasan Education and Social Center, 2024)
This study aims to determine the effect of current ratio, return on assets, and debt to equity ratio on financial distress of PT HM Sampoerna Tbk. The analysis used is quantitative and associative analysis, descriptive test, multiple regression test, classical assumption test, hypothesis testing, determination test. Based on partial tests, current ratio has an influence on financial distress with a regression value of 7.988 and a significance of 0.000, return on assets has an influence on financial distress with a regression value of 9.931 and a significance of 0.000, and debt to equity ratio has an influence on financial distress with a regression value of 2.603 and a significance of 0.035. Based on the simultaneous test, current ratio, return on assets, and debt to equity ratio have an effect on financial distress with a regression value of 168.569 and a significance of 0.000